Thoracalgia in a Patient with Determined Coronary Heart Disease. Is there Always a Relapse of Angina Pectoris? - O. M. Drapkina; A. A. Zeynapur; A. S. Klevina; O. B. Vasileva (Столичная издательская компания, 2020)
This article presents a clinical case of a 62-year-old man with a long history of coronary heart disease and smoking, whose main complaint upon admission to the hospital was voice hoarseness and atypical pain syndrome in the chest. During a preliminary medical examination, attention was paid to the clinical picture, atypical for a coronary heart disease - voice hoarseness was identified as a manifestation of the recurrent nerve compression, or cardio-vocal syndrome. Given the lack of connection between the chest pain and physical exertion, a high index of a smoking person as well as signs of the recurrent nerve compression syndrome, a multi-spiral computer tomography with contrasting of the chest organs was performed (in line with official recommendations of the Russian Associations of Oncologists and Otolaryngologists). The results revealed a proliferative lesion of the mediastinum and multiple focal lesions of both lungs. A subsequent thoracoscopy and biopsy confirmed the mediastinal form of a lung cancer. Promptly initiated poly-chemotherapy allowed stabilizing the patient's condition and significantly improving his prospects. In this context, the article discusses the complexity of a timely diagnosis of a primary lung cancer and emphasizes the need to focus on specific and unique features of the disease course as well as on a broader clinical picture. Tactics of a multidisciplinary approach allows making a diagnosis in a timely manner, significantly improving the effectiveness of therapy and patient's survival prognosis.